INSTITUTIONALIZING DIGITAL PUBLIC RELATIONS: STRENGTHENING GOVERNMENT-CITIZEN ENGAGEMENT THROUGH SOCIAL MEDIA IN MALAYSIA THROUGH INSTITUTIONAL THEORY - Shanmugam, Thinakaridevi; Abdullah, Zulhamri; Mohd Hasan, Nurul Ain; Tham, Jen Sern (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The strategic use of digital public relations (PR) has become increasingly vital for enhancing government-citizen engagement in the digital era. However, in Malaysia, despite the widespread adoption of social media platforms by government agencies, digital PR remains under-institutionalized, with limited leadership commitment, organizational readiness, and formal policy guidance. This conceptual paper addresses this gap by developing a theory-driven framework grounded in Institutional Theory to explain how institutional pressures (regulative, normative, and cultural-cognitive) interact with leadership commitment and organizational readiness to influence digital PR institutionalization. The model further theorizes that institutionalized digital PR enhances citizen trust and engagement quality, two critical dimensions of democratic digital communication. This study contributes to closing a theoretical and contextual gap in Malaysian public sector communication research while offering a framework for policymakers to institutionalize digital PR as a legitimate, sustainable governance function.